Pengaruh Strategi Pengelolaan Produksi Dan Operasi Terhadap Peningkatan Efisiensi Dan Profitabilitas Bisnis Di UD. Gajah Tempur - Eka Dian Puspita; Ilvi Nur Widiana; Ach. Jainur Reo Fajar (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2023)
The purpose of this study was conducted to find out and test whether Production Management Strategy affects Efficiency, does Operation affect Efficiency, does Production Management Strategy affect Profitability, does Operation affect Profitability, and does Efficiency affect Profitability. This research is included in the quantitative research using the Partial Least Square (PLS) method. The population in this study is all consumers in Ud. Elephant Combat, The sample in this study uses a probability sampling design to determine 60 respondents as a sample. The analysis technique in this research is narrative and inferential statistical analysis using the Partial Least Square (PLS) method. as a result of research states that Production Management Strategy affects Profitability, Production Management Strategy influences Efficiency, Operations influences Profitability, Operations influences Efficiency, then Efficiency influences Profitability.